Writing process to improve journalism students’ skills of the Technical University of Babahoyo - Dahik Solis, Cecilia Elizabeth; Feijóo Rojas, Kerly Jazmín; De Mora Litardo, Karina; Caneppa Muñoz, Cecilia Isabel (Journal of Science and Research, 2021)
Since the early days, writing has been considered as one of the most challenging skills to be promoted to students around the world because of writing, in a foreign language, reveals for many studies to be placed at a different level of complexity. On the one hand, the students’ mother tongue interferes with the development of a foreign language, and they are also unwilling to write. On the other hand, other reasons can be connected on why students show difficulties in writing tasks, and that is why writing must be researched deeper. Therefore, this case study attempts to enhance students writing skills of fifth semester students of journalism school through the use of writing process, as well as, Anthony’s quadrants method to gather the evidence. This study is developed in four sections. In the first part, it is detailed the core of the problem and the students’ background in which this case study is focused on. The second part provides reliable information concerning the evidence gotten with the method applied throughout the writing process. The third part states the results and its analysis. In the last part details the conclusions of this case study based on the findings.